2015
DOI: 10.6002/ect.2013.0131
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: In diabetes mellitus type 1, beta cells are mostly destroyed; while in diabetes mellitus type 2, beta cells are reduced by 40% to 60%. We hope that soon, stem cells can be used in diabetes therapy via pancreatic beta cell replacement. Induced pluripotent stem cells are a kind of stem cell taken from an adult somatic cell by "stimulating" certain genes. These induced pluripotent stem cells may be a promising source of cell therapy. This study sought to produce isletlike clusters of insulin-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…For this discovery, a deserving Shinya Yamanaka shared the Nobel Prize in Physiology or Medicine in 2012. Since the Yamanaka protocol was published, several studies have demonstrated the possibility of manipulating adult cells into insulin-producing cells (Thatava et al, 2013 ; Shaer et al, 2015 ). The protocol to produce rich β cell cultures is still being refined and is not without hurdles.…”
Section: Yamanaka Factorsmentioning
confidence: 99%
“…For this discovery, a deserving Shinya Yamanaka shared the Nobel Prize in Physiology or Medicine in 2012. Since the Yamanaka protocol was published, several studies have demonstrated the possibility of manipulating adult cells into insulin-producing cells (Thatava et al, 2013 ; Shaer et al, 2015 ). The protocol to produce rich β cell cultures is still being refined and is not without hurdles.…”
Section: Yamanaka Factorsmentioning
confidence: 99%
“…Human induced pluripotent stem cells hold great promise for tailored cell-based therapies. Functional hiPSC derivatives such as astrocytes, dopaminergic neurons, retinal pigment epithelium cells, adipocyte progenitors, insulin-producing islet-like clusters, bone substitutes, hepatocytes, melanocytes, erythroblasts, cardiomyocytes and red blood cells have already been generated (127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137). Considering damaged tissues account for many chronic illnesses, such as neurodegenerative diseases, retinal degeneration, muscular dystrophy and myocardial infarction, patient-specific hiPSC derivatives can be a suitable therapeutic choice.…”
Section: Potential Application Of Hipscsmentioning
confidence: 99%
“…The Xenopus explant system has been used to generate pancreatic tissue by the utilisation of simple protocols, including an endoderm-inducing factor and RA ( Moriya et al, 2000b ; Chen et al, 2004 ). Protocols for the generation of pancreatic tissue from hESCs or iPSCs similarly include RA, even though such multistep protocols are more complex and include multiple signalling molecules ( Pagliuca et al, 2014 ; Shaer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This same protocol, which was also utilised in the current study, aims to mimic early key regulatory events, given that RA signalling together with inhibition of BMP activity makes it possible to convert ventral endomesodermal explants from gastrula-stage Xenopus embryos to a pancreatic fate ( Pan et al, 2007 ). Similarly, experimental protocols for the in vitro generation of β cells from embryonic stem cells (ESCs) ( Kroon et al, 2008 ; Rezania et al, 2012 ; Schulz et al, 2012 ; Pagliuca et al, 2014 ) or induced pluripotent stem cells (iPSCs) ( Zhang et al, 2009 ; Schiesser et al, 2014 ; Shaer et al, 2015 ) all include application of RA.…”
Section: Introductionmentioning
confidence: 99%